Effects of seagrass overgrazing on sediment erosion and carbon sink capacity: Current understanding and future priorities - Martin Dahl (Wiley, 2021)
Abstract We searched the literature for experimental and observational studies assessing the effects of seagrass overgrazing on erosion of sediment and sedimentary organic carbon (SOC) and found that most studies reported a significant impact, likely caused by a cascading effect (i.e., seagrass shoot loss → belowground biomass degradation → sediment destabilization or SOC erosion). However, there appears to be a clear lack of knowledge on the extent and mechanisms behind SOC erosion in seagrass meadows and we highlight the need for research to (1) define spatial and temporal scales of occurrence; (2) assess the influence of belowground biomass degradation, sediment characteristics, and hydrodynamic exposure on sediment stabilization; and (3) estimate the greenhouse gas emission after a disturbance. Such information would help coastal resource managers to address the causes and effects of SOC loss and sediment erosion when evaluating impacts of global change on coastal ecosystems.